2018
DOI: 10.1111/add.14136
|View full text |Cite
|
Sign up to set email alerts
|

Medical marijuana laws and adolescent marijuana use in the United States: a systematic review and meta‐analysis

Abstract: AimsTo conduct a systematic review and meta‐analysis of studies in order to estimate the effect of US medical marijuana laws (MMLs) on past‐month marijuana use prevalence among adolescents.MethodsA total of 2999 papers from 17 literature sources were screened systematically. Eleven studies, developed from four ongoing large national surveys, were meta‐analyzed. Estimates of MML effects on any past‐month marijuana use prevalence from included studies were obtained from comparisons of pre–post MML changes in MML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 91 publications
6
112
2
1
Order By: Relevance
“…M. Anderson et al, 2014; Choi, 2014; Choo et al, 2014; Harper et al, 2012; D. S. Hasin et al, 2015; Johnson, 2015; Johnson et al, 2017; Keyes et al, 2016; Martins et al, 2016; Pacula et al, 2015; Sarvet et al, 2018; Smart, 2015; Wall et al, 2016; Wen et al, 2015). In contrast, four studies using large surveys and similar methodology found MCLs to be associated with increases in cannabis use among adults (Chu, 2014; D.…”
Section: Discussionmentioning
confidence: 99%
“…M. Anderson et al, 2014; Choi, 2014; Choo et al, 2014; Harper et al, 2012; D. S. Hasin et al, 2015; Johnson, 2015; Johnson et al, 2017; Keyes et al, 2016; Martins et al, 2016; Pacula et al, 2015; Sarvet et al, 2018; Smart, 2015; Wall et al, 2016; Wen et al, 2015). In contrast, four studies using large surveys and similar methodology found MCLs to be associated with increases in cannabis use among adults (Chu, 2014; D.…”
Section: Discussionmentioning
confidence: 99%
“…These declines are part of a broader trend towards delayed adult activities (e.g. Declines in marijuana use, deviance and risk preference in youth are also occurring in the context of changing medical marijuana laws, which have not been causally related to changes in marijuana use in youth in a recent meta-analysis [47] or affected perceived availailability of marijuana use at ages 12-17 years [12]. These delays are often attributed to a greater parental investment (due to older age of childbearing and fewer children) [43,44], general economic prosperity prior to the Great Recession and a change in how adolescents interact due to technology, that allows interaction without unsupervised time alone with other adolescents, which is when deviant activities and experimentation with drug use often occur [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…These fears are probably overblown, and not just because cannabis is far less lethal than opioids 18. Legalising medical marijuana, with relatively liberal access, has not caused major increases in cannabis use in the US 19. Indeed, there are some indications that it has reduced harms associated with opioid analgesics, including deaths from overdose and workplace or traffic injuries 202122…”
Section: Patient Autonomy Versus Controlled Prescriptionmentioning
confidence: 99%